Changes in resonance frequency analysis assessed by Osstell mentor during osseointegration: comparison between immediately loaded implants and control implants without load - M. González-Jaranay; G. Moreu-Burgos; G. Gómez-Moreno; J Rubio-Roldán; G. Machuca-Portillo; V. Perrotti; A. Boquete-Castro; J.L. Calvo-Guirado (Ariesdue, 2014)
Aim: The aim of this prospective clinical study was to evaluate the changes in resonance frequency analysis (RFA), assessed by Osstell Mentor, obtaining information on the implant stability quotient (ISQ) during implants tissue integration for immediately loaded and non-loaded control implants. Materials and methods: A total of 40 implants, 20 implants with no immediate loading (control) and 20 immediately loaded implants (test), were placed in 15 patients. ISQ implants was evaluated at baseline and at 6 and 8 weeks. Provisional crowns were removed at 8 weeks, when the definitive restoration was placed. Data of control and test implants and maxillary and mandibular areas were statistically compared. Results: At 8 weeks, all implants were integrated and there were no major postoperative complications. A statistically significant difference was found only at baseline between test and control maxillary implants (p=0.009) but not at 6 or 8 weeks (p>0.05). Conclusion: Immediate loading procedures may be applied with primary stability ISQ values >60 and inserted with a force of ≥30 N. The Osstell Mentor RFA may offer an objective method to determine when implant stability is adequate for immediate loading.